Recurrent lumbar disc herniation: Results of surgical treatment in patients entitle to a worker's compensation program (2008)
Recurrent lumbar disc herniation is the main cause of radicular pain after lumbar discectomy, with a reported incidence between 5 and 12.5%. Objectives: Evaluate the results of surgical treatment for recurrent lumbar disc herniation in patients subject to a workers' Compensation program. Methods: We reviewed the medical records of the 663 patients subject to workers compensation, treated with discectomy for a lumbar disc herniation by the Spine Unit of the 'Hospital del Trabajador' between January 1996 and June 2006. We then selected our study group, the subset of these patients who underwent spine surgery for the first recurrence of their lumbar disc herniation during the described period of time. We used chi2 to analyze non parametric variables and T-test to analyze parametric variables, accepting statically significance with a p value less than 0.05. Results: Eight hundred one patients required a second spine surgery for the first recurrence of a lumbar disc herniation, with a mean follow-up of 75 months (14-137). The mean time off work rest after surgery was 69.3 days. 14.8% of the patients received compensation with a median 25% of loss of work capacity. Surgery related complications were observed in 2.4% of the patients (one incidental durotomy and one surgical wound infection). Conclusion: Spine surgery for the first recurrence of a lumbar disc herniation, in patients subject to a workers' compensation program has equivalent results to the primary surgery, as regarded to length of work rest, secondary incapacity and complications.